2013
DOI: 10.1016/j.cub.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Instant Transformation of Learned Repulsion into Motivational “Wanting”

Abstract: Summary Background Learned cues for pleasant rewards often elicit desire, which in addicts may become compulsive. According to the dominant view in addiction neuroscience and reinforcement modeling, such desires are the simple products of learning, coming from past association with reward outcome. Results We demonstrate that cravings are more than merely the product of accumulated pleasure memories: even a repulsive learned cue for unpleasantness can become suddenly desired via activation of mesocorticolimb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
240
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(257 citation statements)
references
References 32 publications
14
240
1
2
Order By: Relevance
“…To the best of our knowledge, this is the first demonstration that the attentional modulation of rewardassociated stimuli critically depends on the flexible representation of the properties of the associated reward. The fact that attentional orienting is modulated by reward devaluation is congruent with experiments showing that reward devaluation procedures modulate behavior (e.g., Wellman et al, 2005) and brain activity (Gottfried et al, 2003) evoked by the reward-associated stimuli Recently, Robinson and Berridge (2013) have underlined the importance of the relevance of the reward's representation for the reactions elicited by reward-associated stimuli. They demonstrated that it is not only possible to diminish the behavioral reactions elicited by a CS through reward devaluation, but that it is also possible to amplify them by increasing the relevance of the associated reward for the current needs of the organism.…”
Section: Discussionsupporting
confidence: 67%
“…To the best of our knowledge, this is the first demonstration that the attentional modulation of rewardassociated stimuli critically depends on the flexible representation of the properties of the associated reward. The fact that attentional orienting is modulated by reward devaluation is congruent with experiments showing that reward devaluation procedures modulate behavior (e.g., Wellman et al, 2005) and brain activity (Gottfried et al, 2003) evoked by the reward-associated stimuli Recently, Robinson and Berridge (2013) have underlined the importance of the relevance of the reward's representation for the reactions elicited by reward-associated stimuli. They demonstrated that it is not only possible to diminish the behavioral reactions elicited by a CS through reward devaluation, but that it is also possible to amplify them by increasing the relevance of the associated reward for the current needs of the organism.…”
Section: Discussionsupporting
confidence: 67%
“…It suggests, thus, that sign-trackers need a phasic dopaminergic prediction-error signal in order to learn because their learning is heavily biased towards learning through incremental acquisition of model-free values V MF (s). The fact that the signals are observed in the NAcc core also maps onto the notion that these signals might be model-free because, as discussed above, model-free mechanisms suffice for general PIT, which is dependent on the core, but not for specific PIT, which is more dependent on the shell (section 4.4; Corbit and Balleine 2011; though see (Shiflett and Balleine, 2010;Robinson and Berridge, 2013)). Finally, the reliance on model-free learning can, at least in part, explain the core incentive salience features.…”
Section: Dopamine Signals During Acquisitionmentioning
confidence: 95%
“…Importantly, sign-tracking behavior was fully impaired upon the first CS-US presentation following administration of flupenthixol into the accumbens. Thus, the drug effects were evident before new learning could occur, and changes in in dopamine levels were able to alter the motivational value of reward cues, without the need to re-experience the CS-US association (Berridge, 2012;Richard et al, 2013;Dayan and Berridge, 2013;Robinson and Berridge, 2013). Furthermore, the effects of dopamine antagonism were specific to the Pavlovian conditioned approach behavior and did not affect the conditioned orienting response in the sign-trackers .…”
Section: Dopamine Signals During Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of neurons to flexibly respond to reinforcers with either approach or avoidance behaviors also facilitates the explanation of counterintuitive behavioral choices. For example, extremely salty solutions are typically avoided, but physiological salt deprivation will produce approach behavior for salty reinforcers (Robinson and Berridge 2013). Also, cues that predict punishing reinforcers are also sometimes chosen over cues that predict the absence of any reinforcer (Barberini et al 2012).…”
Section: Models For Segregated Function In the Blamentioning
confidence: 99%